Relationship between Perceived Ease of Use and Perceived Usefulness towards Adoption Intention of Smart Home Technology among Government Servants in Kinta, Perak - Ivy Lim Jeng Yee,; Nor Kamariah Kamaruddin, (Research in Management of Technology and Business, 2024)
The rapid advancement of technology has brought significant changes in various aspects of our daily lives, including our homes. The growth of the Internet of Things (IoT) is still at its early stages. However, previous research often lacks focus on understanding the issue from the perspective of specific customers. Government servants play a crucial role in the implementation and adoption intention of smart city initiatives because they are the backbone of the country. Perceived ease of use and perceived usefulness are two critical factors that influence a person’s perspective and attitude towards adoption intention technology. Exploring government servants’ intention to adopt smart home technology is critical. The study aims to investigate the relationship between perceived ease of use and perceived usefulness correlated with government servants’ adoption intention to use smart home technology in Kinta, Perak. The surveys were distributed through WhatsApp and physical distribution with 80% response rate (182 out of 226 respondents). Based on the descriptive analysis, adoption intention to used smart home technology perceived ease of use, perceived usefulness had a high mean score. As for Spearman’s Correlation Coefficient analysis, showed a strongest relationship between two independent variables of perceived ease of use and perceived usefulness with adoption intention of smart home technology. The discovered insights could provide valuable guidance for Smart Home developers aiming to grasp the inclinations of government servants regarding the adoption of Smart Home Technology.